Analisis Faktor-Faktor Yang Memengaruhi Stock Return Dengan Investment Opportunity Set Sebagai Intervening - Fennisya Dewangga, Herlin Tundjung (Jurnal Paradigma Akuntansi, 2021)
This research aims to analyze the effect of dividend policy, leverage, profitability, and firm value on stock returns and to analyze the effect of firm value toward stock return with Investment Opportunity Set as Intervening in manufacturing companies listed on Indonesia Stock Exchange in 2017-2019. Samples were taken based on purposive sampling method of 35 companies, so data amounted to 105. This research used secondary data, obtained  from the website https://idx.co.id/. Data analysis technique used are descriptive statistics and Partial Least Square test processed by SmartPLS 3.3.2 program. The results of this research indicate that dividend policy and firm value have negative and significant effect on stock returns, profitability and Investment Opportunity Set have positive and significant effect on stock returns, leverage has no significant effect on stock returns, and Investment Opportunity Set mediates the effect of firm value on stock returns. The implication of this research is to analyze company’s performance and prospects as a signal for making investment decisions and minimize investment risk.